2018
DOI: 10.1080/15384047.2016.1210743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel metabolic-related mutation (IDH1) in metastatic pancreatic cancer

Abstract: Isocitrate dehydrogenase 1 (IDH1) is a metabolic enzyme implicated in cancer cell metabolic reprogramming. This is underscored by the detection of functional, somatic IDH1 mutations frequently found in secondary glioblastoma. To our knowledge, there has never been a reported, validated case of an IDH1 mutation in a pancreatic ductal adenocarcinoma (PDA). Herein, we present a case of a patient with metastatic PDA that harbored a potentially actionable, albeit rare, IDH1 mutation. As part of the Know Your Tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 39 publications
(46 reference statements)
0
39
0
Order By: Relevance
“…IDH1 has been the subject of numerous studies in the cancer research field because of its high mutation frequency in many cancers (36). Of note, this genetic abnormality is exceptionally rare in PDAC, and has only recently been reported in a single case by our group (37). We theorize that the rarity of this mutation in PDAC is related to the deleterious effect that has been ascribed to haploinsufficiency of the wild type allele under very austere conditions (38).…”
Section: Discussionmentioning
confidence: 54%
“…IDH1 has been the subject of numerous studies in the cancer research field because of its high mutation frequency in many cancers (36). Of note, this genetic abnormality is exceptionally rare in PDAC, and has only recently been reported in a single case by our group (37). We theorize that the rarity of this mutation in PDAC is related to the deleterious effect that has been ascribed to haploinsufficiency of the wild type allele under very austere conditions (38).…”
Section: Discussionmentioning
confidence: 54%
“…For instance, we recently demonstrated that pancreatic cancers, which do not have IDH1 mutations, rely on WT.IDH1 expression to generate reductive power needed to combat severe oxidative stress ubiquitously present in the tumor microenvironment (11,25). For this reason, our group has postulated that IDH1 mutations may even be deleterious in pancreatic cancer due to the characteristically harsh microenvironment (16) and could account for the rarity of this genetic alteration in that lethal cancer (3). Others have shown the importance of WT.IDH1 for reductive carboxylation and lipogenesis under hypoxic conditions in other IDH1 wild-type cancers (e.g., lung; refs.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the RNA stability factor, HuR (ELAVL1), regulates WT.IDH1 transcript expression in pancreatic cancer (which do not typically acquire IDH1 mutations; ref. 16). Mechanistically, the RNA-binding protein affects mRNA expression by first recognizing and binding AU-rich RNA elements within specific mRNA 3 0 untranslated regions (3 0 UTR; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Additional highly actionable altered genes included receptor tyrosine kinases (RTK), including activating mutations in ERBB2 (17, 2.8%) and several oncogenic fusions: CCDC6-RET, NCOA4-RET, STRN-ALK, LMNA-NTRK1, and ETV6-NTRK3. Three activating mutations in codon 132 of IDH1 were also observed (22).…”
Section: Genomic Alterations Detected By Ngsmentioning
confidence: 97%